Disparities in emergency department access, resource allocation, and outcomes between migrants and the local population (Swiss Medical Weekly, 2021)
AIMS: To characterize a group of migrant emergency department (ED) patients regarding demographics, access to the ED, mode of referral, use of resources, and short-term outcomes, and to compare them to a group of local ED patients. METHODS: Prospective cohort study with consecutive enrollment of adult patients presenting to the ED of a Swiss tertiary care hospital from October 21st to November 11th, 2013 and February 1st to February 23rd, 2015. In accordance with the International Organization for Migration, we defined migrants as persons who have changed their country of usual residence, irrespective of their legal status. The primary outcome was defined as the number of resources allocated to migrants, as compared to local patients, using uni- and multivariable quasi-Poisson regressions. Acute morbidity, hospitalization, intensive care unit (ICU) admission, and 30-day mortality were assessed as secondary outcomes. RESULTS: Migrant patients were younger, more often male and self-presenters, and of lower acuity. After adjustment for age, gender and acuity, we observed a non-significant difference of 3.6% in the mean number of resources allocated to migrant patients as compared to local patients (adjusted RR 0.964, CI 0.923-1.006). No difference in 30-day mortality (adjusted OR 0.777, CI 0.346-1.559) was observed between the two patient groups, but migrant patients had lower odds of acute morbidity (adjusted OR 0.652, CI 0.560-0.759), hospitalization (adjusted OR 0.666, CI 0.555-0.799), and ICU admission (adjusted OR 0.649, CI 0.456-0.910). CONCLUSIONS: ED access approximation, resource allocation, and mortality were comparable between migrant patients and local patients. Lower admission rates to wards and the ICU may raise concerns but can be explained by lower acute morbidity in migrant patients.